Prevalence and Mycotoxigenic Potential of Fungi in Fish Feed Collected from Fish Farms in Egypt with a Particular Reference to Aflatoxins Contamination - Galal, Yasmen; El-Bana, Magdy; Deabes, Mohamed M.; Rasmey, Abdel-Hamied M. (Journal of Advanced Veterinary Research, 2024)
The current study is aimed to investigate the fungal contaminants in fish feed. Isolation of fungi was conducted on modified dichloran 18% glycerol agar (DG18) and potato dextrose agar (PDA). Feed samples were assayed for aflatoxins using HPLC. A total of 43 species belonging to 19 fungal genera recovered from 45 fish feed samples. Aspergillus and Penicillium were the most predominant genera with isolation frequency values indicated the retrieval capability of DG18 over PDA medium. For instance, Aspergillus spp. recorded 60%, 53.3% while Penicillium spp. were 33.3%, 17.8% on DG18 and PDA respectively via direct plating. 41.4% of the tested isolates were mycotoxin producers. Aflatoxins B1, B2, G1 and G2 were detected by 6 out of 10 screened Aspergillus isolates. Fumitremorgens, Gliotoxin, Ochratoxin A and B, and Zeralenone were also detected. The feed samples of high total count percentages (TC%) of A. flavus recorded the highest incidence of aflatoxins B2, G1 and G2 (2.3, 35.3 and 7.8 ng/g respectively). Meanwhile, the highest B1 concentration (3.7 ng/g) was recorded for the highest TC% interval studied (1:9 cfu/g). Thus, it is important to monitor the fungal load and mycotoxins in fish feed periodically using proper practical approaches.